Neuroimaging, hormonal and genetic biomarkers for pathological aggression — success or failure?. (February 2022) - Wagels, Lisa; Habel, Ute; Raine, Adrian; Clemens, Benjamin
Abstract : Aggression affects nearly all mental disorders and constitutes a burden for society in general and the mental health sector in particular. An incomplete understanding of its underlying neurobiological mechanisms limits treatment efficacy and hinders the development of precision medicine approaches. Here we review recent efforts employing neuroimaging, hormonal and (epi)genetic data to develop biomarkers for aggression. Our goal is to discuss limitations of these previous studies and propose strategies which may help overcome these limitations in order to achieve both: transdiagnostic classification and prediction of individual treatment outcomes. In order to develop clinically relevant biomarkers for aggression, candidate biomarkers have to be combined and their reliability and validity has to be tested rigorously in large patient cohorts. Besides generating a better mechanistic understanding, we should strive to create multimodal biomarkers that medical professionals can utilize in clinical practice to guide and improve the management and clinical outcome of pathological aggression.